POLÍTICAS PÚBLICAS EM CIÊNCIA E TECNOLOGIA NO BRASIL: A LEI DA INOVAÇÃO E A LEI DO BEM - Silva, Sérgio Murilo Archanjo da (2008)
This work has the objective to examine the different routes of science, also the technology and innovation in Brazil, considering the Law of Innovation and that I call "the Law of the Good , to strengthen the National System of Science and Technology. The objective of this work is to intensify the association between the several agencies under the Ministry of Science and Technology, other entities of the Government, companies, university and research centers. This work identifies the worries about the area of economy referring the capacity of the State to provide the welfare of the citizens, and in environmental matters-necessity to establish collective agreements to conserve or to preserve the welfare. These considerations suggest measure of incentive to the innovation and the scientific and technological research in the productive environment aiming the qualification and the technological autonomy the industrial development of the country. An ample specter of governmental instruments, are presented to promote of the Research and Development - industrial P&D is presented. To conclude this work was carried but are critical look the area of scientific and technological, the results showed that state policies related to innovation is significant weak. The discussed laws it is a strong point that should be considered in the Law of Innovation and the Law of the Good for the future. In looking for Democracy and Excellency it has shown the first few years of the implementation of these laws, has to permit to think that the institutions involved this matter showed to carry or Deeping these discussions.